대학 혁신과 디지털 전환에 적합한 리서치 코디네이터(RC)의 역할 분석 - 조윤희(Yoon-Heui Cho); 유신열(Shin-Ryul Yu); 허성호(Sung-Ho Hu) (디지털콘텐츠학회논문지, 2023)
본 연구의 목적은 대학 혁신과 디지털 전환에 필요한 리서치 코디네이터의 역할을 탐색하는 것이다. 연구설계는 시기와 관점의 두가지 요소를 중심으로 구분하여 분석을 실시하였다. 시기별로 Covid19 전과 후를 구분하여 분석하였고, 관점별로는 내부적 관점과 외부적 관점으로 구분하여 분석하였다. 분석방법은 빅데이터분석 방법인 TEVA 모형을 적용하여 분석하였고, 키워드 분석, 연관어 분석, 군집 분석, ANOVA를 실시하였다. 연구결과, RC 역할은 26개의 키워드로 나타났다. Covid19 이전 시기에는 대학, 융합, 연구자가 중요한 키워드였고, Covid19 이후 시기에는 정보, 지원, 공유가 중요한 키워드인 것으로 나타났다. 내부적 관점에서는 기획, 사업, 전문이 중요한 키워드였고, 외부적 관점에서는 연구자, 융합이 중요한 키워드인 것으로 나타났다. 연관어 분석에서 중심성은 전체적으로 기획, 과제 중심으로 구조화 되어 있는 것으로 나타났다. 아울러, RC 역할은 시기별 관점별 상호작용이 나타났다. 이러한 결과들을 중심으로 학술적, 제도적, 문화적인 논의점을 제시하였다. This study aimed to explore the role of research coordinators necessary for the digital transformation of universities. The study design was analyzed by dividing it into two elements: time and perspective. It was analyzed by dividing before and after Covid19 by period and by dividing it into internal and external viewpoints by perspective. The analysis method was analyzed by applying the TEVA model, which is a big data analysis method, and keyword analysis, related word analysis, cluster analysis, and ANOVA were performed. As a result of the study, the role of RC was represented by 26 keywords. In the period Covid19-pre, university, convergence, and researcher were important keywords, and in the Covid19-post period, information, support, and share were found to be important keywords. From an internal perspective, plan, business, and specialty were important keywords; from an external perspective, researcher and convergence were found to be important. In the analysis of related words, centrality was found to be structured around plan and project as a whole. In addition, the role of RC showed interactions by time and perspective. Based on these results, academic, institutional, and cultural points of discussion were presented. KCI Citation Count: 0